2016
DOI: 10.2134/ael2016.08.0032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rising Plate Meter for Use in Multispecies Swards

Abstract: Core Ideas The accuracy of rising plate meter in multispecies swards has not been tested thoroughly. Forcing X intercept to zero increases the precision of the calibration equations. Higher‐order polynomial regressions do not result in more accurate forage estimates. The rising plate meter (RPM) provides rapid estimates of herbage mass (HM). Accurate calibration of the RPM is difficult due to variability in forage management, growth, and species composition. The RPM is typically calibrated by linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Brito et al (2017) observed a similar botanical composition pattern in herbage samples collected throughout the grazing season. In these 2 studies, the mean proportion of grasses (51%) was 2.8-fold greater than the mean proportion of legumes (18%), which agrees with our previous work conducted in commercial dairies under organic certification (Dillard et al, 2016;Hafla et al, 2016). Herbage CP concentration followed the proportion of legumes and fluctuated across the grazing season, with numerically lowest values in wk 4 and 12 and greatest in wk 8 and 16 (Table 1).…”
Section: Herbage Mass and Feed Nutritional Compositionsupporting
confidence: 89%
“…Brito et al (2017) observed a similar botanical composition pattern in herbage samples collected throughout the grazing season. In these 2 studies, the mean proportion of grasses (51%) was 2.8-fold greater than the mean proportion of legumes (18%), which agrees with our previous work conducted in commercial dairies under organic certification (Dillard et al, 2016;Hafla et al, 2016). Herbage CP concentration followed the proportion of legumes and fluctuated across the grazing season, with numerically lowest values in wk 4 and 12 and greatest in wk 8 and 16 (Table 1).…”
Section: Herbage Mass and Feed Nutritional Compositionsupporting
confidence: 89%
“…The botanical and nutritional composition of the mixed grass-legume herbage is presented in Table 1. Herbage mass production averaged 2,425 kg of DM/ha and was within the range observed in the northeastern United States for similar perennial cool-season pastures under organic certification (Dillard et al, 2016). The proportion of grasses was numerically greatest in wk 3 and relatively similar in wk 7, 12, and 15, whereas that of legumes and weeds was numerically lowest in wk 3 and increased substantially thereafter.…”
Section: Nutritional Composition Of Herbage and Feedssupporting
confidence: 67%
“…Past literature usually used a linear functional form, while Rayburn et al (2017) suggested a quadratic model with no intercept. Dillard et al (2016) found support for the no‐intercept restriction. The two models are non‐nested since neither one can be estimated as a special case of the other one.…”
Section: Data Collection and Statistical Analysismentioning
confidence: 98%
“…Studies have dealt mostly with ryegrass ( Lolium perenne L.) and clovers ( Trifolium repens L.) and have been most interested in grazing for sheep (Bryant et al, 2017; Scrivner et al, 1986). Research has considered ryegrass (Nakagami and Itano, 2014), chicory ( Cichorium intybus L.) and plantain ( Plantago L.) (Haultain et al, 2014), and a mix of grasses (Dillard et al, 2016). Calibration equations are often estimated separately for month or season (Scrivner et al, 1986; L'Huillier and Thomson, 1988; Nobilly et al, 2013).…”
mentioning
confidence: 99%